Walking assist device : the electronic and firmware design - Sim, K. S. (2013)
This project aims to design and develop a working prototype of a walking assist device. Spring and brushed DC motors are adopted to assist human being standing or walking by lessening the amount of force subjected to the knee. Two DC motors are controlled by the high current capable motor driver which is specifically designed for heat management. Moreover, an 8051 microcontroller provides interface between the sensor ADC input, keypad manual input, intelligent controller and the DC motors.